2017
DOI: 10.1002/bab.1576
|View full text |Cite
|
Sign up to set email alerts
|

Role of Q177A and K173A/Q177A substitutions in thermostability and activity of the ELBn12 lipase

Abstract: Thermostable lipases have many applications in detergent industries and in organic synthesis. There are many ways to improve thermal stability of enzymes, for example, higher hydrophobicity, greater structural packing, higher content of the charged residues, and lower thermolabile ones. In this study, thermolabile Gln (sensitive to higher temperatures) was substituted with Ala in native ELBn12 and mutated K173A lipases to examine its effect on thermal stability and activity of the lipases. Single (Q177A) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This genetic method is called thermorecovery, which could be used for the biofuel feedstock collection. Other thermostable lipases seem to be appropriate candidates for making engineered cyanobacteria with the capability to release FFA.…”
Section: Genetically Engineered Cyanobacteriamentioning
confidence: 99%
“…This genetic method is called thermorecovery, which could be used for the biofuel feedstock collection. Other thermostable lipases seem to be appropriate candidates for making engineered cyanobacteria with the capability to release FFA.…”
Section: Genetically Engineered Cyanobacteriamentioning
confidence: 99%
“…Currently, many protein engineering methods have been developed to improve esterases (or lipases) properties, including substrate specificity [41,42], activity [43,44], thermostability [45], and enantioselectivity [46,47]. However, limited studies for enhancing alkali tolerance have been reported, especially based on structural information.…”
Section: Discussionmentioning
confidence: 99%
“…S5). According to previous studies, the thermal stability can be affected by (i) more abundant, high hydrophobicity, charged residues (such as Glu, Arg, and Lys) rather than uncharged polar amino acid (such as Ser, Thr, Asn, and Gln) in the amino acid sequences [41,48,49]; (ii) more α-helices in structures [50,51]; and (iii) some intermolecular forces, such as hydrogen bonds [52]. AlinE4 has 6 glutamine residues and 12 lysine residues, while CrmE10 has 12 glutamine residues and only 1 lysine residue, which might lead to the difference in thermal stability.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many protein engineering methods have been developed to improve esterases (or lipases) properties, including substrate speci city [41,42], activity [43,44], thermostability [45], and enantioselectivity [46,47]. However, limited studies for enhancing alkali-tolerance have been reported, especially based on structural information.…”
Section: Discussionmentioning
confidence: 99%
“…S5). According to previous studies, the thermal stability can be affected by (i) more abundant, high hydrophobicity, charged residues (such as Glu, Arg, and Lys) rather than uncharged polar amino acid (such as Ser, Thr, Asn, and Gln) in the amino acid sequences [41,48,49]; (ii) more α-helices in structures [50,51]; and (iii) some intermolecular forces, such as hydrogen bonds [52]. AlinE4 has six glutamine residues and twelve lysine residues, while CrmE10 has twelve glutamine residues and only one lysine residue, which might lead to the difference in thermal stability.…”
Section: Discussionmentioning
confidence: 99%